EFFECTS OF NUTRIENT SOURCES AND VARIETY ON THE GROWTH AND YIELD OF SORGHUM (Sorghum bicolor L. Moench) IN BAUCHI STATE NIGERIA - Shuaibu, Y. M.; Nayaya, J. A.; Bala, R. A.; Sabo M. U.; Abdu, A. I.; Abdulkadir S. U. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The experiment was conducted at Bauchi State College of Agriculture (10o22’N and 9o47’E), in the northern guinea savannah zone of Nigeria, during the rainy season of 2018 to study the effect of nutrient sources and variety on the growth and yield of sorghum. The treatment consisted of four nutrient sources (chicken feather, mineral fertilizer, municipal waste, poultry manure) and control and two varieties of sorghum which are (CSR-01 and SK-5912), these were factorialy combined to give 10 treatment combinations and laid out in Randomized Complete Block Design (RCBD) replicated three times. All data collected were subjected to analysis of variance (ANOVA) and Duncan Multiple Range Test (DMRT) was adopted in separating the means. The result of the experiment indicated that no significant (P≤0.05) difference observed throughout the study period with regards to the varieties used, but there is a significant (P≤0.05) difference among the nutrient sources used. The result further revealed that application of 30kg/ha NPK was found to be significantly (P≤0.05) better than other nutrient sources. Based on the finding of this experiment, nutrient source can be used as a means of improving soil condition for sustainable sorghum production.